Cytotoxic studies of paclitaxel (Taxol) in human tumour cell lines. - Liebmann, J. E. (Nature Publishing Group, 1993)
The cytotoxicity of paclitaxel against eight human tumour cell lines has been studied with in vitro clonogenic assays. The fraction of surviving cells fell sharply after exposure for 24 h to paclitaxel concentrations ranging from 2 to 20 nM; the paclitaxel IC50 was found to range between 2.5 and 7.5 nM. Increasing the paclitaxel concentration above 50 nM, however, resulted in no additional cytotoxicity after a 24 h drug exposure. Cells incubated in very high concentrations of paclitaxel (10,000 nM) had an increase in survival compared with cells treated with lower concentrations of the drug. Prolonging the time of exposure of cells to paclitaxel from 24 to 72 h increased cytotoxicity from 5 to 200 fold in different cell lines. Exponentially growing cells were more sensitive to paclitaxel than were cells in the plateau phase of growth. Cremophor EL, the diluent in which the clinical preparation of paclitaxel is formulated, antagonised paclitaxel at concentrations of 0.135% (v/v). These data suggest that paclitaxel will be most effective clinically when there is prolonged exposure of tumour to the drug. Further, it appears that modest concentrations (i.e., 50 nM) should be as effective as higher concentrations of paclitaxel. Finally, we have noted that Cremophor EL is a biologically active diluent and, at high concentrations (0.135% v/v), can antagonise paclitaxel cytotoxicity.